Determination of triplet excitons in organic semiconductor materials. Issue 1629 (22nd January 2014) - Döring, S.; Riedl, T.; Rabe, T.; Kowalsky, W.
ABSTRACT: The formation of triplet excitons in semiconducting organic materials plays an important role for the operation of organic optoelectronic devices. Triplet excitons are difficult to investigate spectroscopically at room temperature due to their non-radiative character. Here we show the measurement of the triplet decay dynamics by a highly sensitive time-resolved measurement of the triplet state absorption using pump and probe experiments within a waveguide configuration. Pump and probe pulse have to be separated spatially and in time to ensure a segregation of singlet and triplet excitons. The non-radiative triplet excitons are detected at room temperature by their absorption. A variation of the time delay between pump and probe pulse allows for the investigation of the dynamics of the excitons. Former experiments made use of the photoluminescence of the material under investigation itself as source of probe light. But since there is a spectral shift between the photoluminescence band and the triplet absorption band the spectral bandwidth of probe light has to be broadened for the identification of the triplet absorption. Here we show how a widening of the probe light band up to red part of the spectrum is achieved by an application of extra emission layers. With the help of this technique the triplet exciton dynamics of the hole transport material 2, 2', 7, 7'-tetrakis(diphenylamino)-9, 9'-spirobifluorene (SpiroTAD) was measured and analyzed.